Lobectomy offers improved survival outcomes relative to segmentectomy for >2 but ≤4 cm non–small cell lung cancer tumorsCentral MessagePerspective - Terrance Peng, MD, MPH; Sean C. Wightman, MD; Li Ding, MD, MPH; Dustin K. Lieu, MD; Scott M. Atay, MD; Elizabeth A. David, MD, MAS; Anthony W. Kim, MD (JTCVS Open, 2022)
Objective: The objective was to compare overall survival (OS) between lobectomy and segmentectomy for patients with non–small cell lung cancers (NSCLCs) > 2 but ≤4 cm. Methods: The National Cancer Database was queried to identify treatment-naïve patients with NSCLC tumors >2 but ≤4 cm. Eligible patients were diagnosed with pT1 or T2 N0 M0 disease, underwent lobectomy or segmentectomy, and received no adjuvant therapy. OS was compared using the Kaplan-Meier method, and the Cox proportional-hazards model was used to identify prognostic factors for death. Propensity score matching was performed to minimize the effects of potential confounders. Results: Included were 32,792 patients: lobectomy (n = 31,353) and segmentectomy (n = 1439). Five-year OS was improved following lobectomy over segmentectomy for patients with >2 but ≤4 cm NSCLCs (62.3% vs 52.6%; P < .0001). Further stratification demonstrated improved 5-year OS following lobectomy over segmentectomy: >2 but ≤3 cm (64.9% vs 54.3%; P < .0001) and >3 but ≤4 cm (56.9% vs 47.6%; P = .0003). In patients with a Charlson-Deyo comorbidity index of 0, 5-year OS was greater following lobectomy for >2 but ≤4 cm tumors (67.1% vs 62.1%; P = .03). Further stratification demonstrated improved 5-year OS following lobectomy for patients with Charlson-Deyo comorbidity index of 0 and > 3 but ≤4 cm tumors (61.8% vs 54.6%; P = .02). Segmentectomy was prognostic for increased risk of death in the year 1 through 5 postoperative period (hazard ratio, 1.35; P < .0001). Five-year OS remained greater following lobectomy after propensity score matching (59.6% vs 52.7%; P = .02). Conclusions: Lobectomy is associated with superior 5-year OS compared with segmentectomy and may be preferred for NSCLC tumors >2 but ≤4 cm when feasible.